2004
DOI: 10.1023/b:nere.0000029569.20266.3f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Anandamide and Synthetic Cannabimimetics of the Release of [3H]d-Aspartate and [3H]GABA from Synaptosomes Isolated from the Rat Hippocampus

Abstract: Cannabinoids (CB) can act as retrograde synaptic mediators of depolarization-induced suppression of inhibition or excitation in hippocampus. This mechanism may underlie the impairment of some cognitive processes produced by these compounds, including short-term memory formation in the hippocampus. In this study, we investigated several compounds known to interact with CB receptors, evaluating their effects on K(+)-evoked release of [3H]D-aspartate ([3H]D-ASP) and [3H]GABA from superfused synaptosomes isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Alternatively, the effect of anandamide and flufenamic acid could be indirect. Flufenamic acid blocks other channel types (54), while anandamide is a general inhibitor of secretion in neuronal cells and is a natural ligand for cannabinoid and TRPV1 receptors (30,31), the latter of which we previously showed to be required for ATP release by the bladder uroepithelium (55). We also observed that verapamil and dipyridamole significantly impaired ATP release, which implicates ABC and nucleoside transporters.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Alternatively, the effect of anandamide and flufenamic acid could be indirect. Flufenamic acid blocks other channel types (54), while anandamide is a general inhibitor of secretion in neuronal cells and is a natural ligand for cannabinoid and TRPV1 receptors (30,31), the latter of which we previously showed to be required for ATP release by the bladder uroepithelium (55). We also observed that verapamil and dipyridamole significantly impaired ATP release, which implicates ABC and nucleoside transporters.…”
Section: Discussionsupporting
confidence: 60%
“…The general secretion inhibitor brefeldin A (BFA) dramatically reduced the release of ATP into the serosal and mucosal hemichambers ( Figure 1, A and B). Anandamide, which can block release of ATP through connexin hemichannels (8) but also acts as a ligand for cannabinoid and transient receptor potential vanilloid 1 (TRPV1) channels (30,31), markedly reduced serosal and mucosal release of ATP ( Figure 1, A and B). In contrast, flufenamic acid, which also inhibits ATP transport through connexin hemichannels (8,32), impaired mucosal but not serosal release of ATP ( Figure 1, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it cannot be ruled out that the efficacy of GABA-ergic connections made by interneurons from some other subpopulation can still be significantly modulated by capsaicin. The latter possibility is indirectly supported by the observation that the release of GABA from synaptosomes isolated from the rat hippocampus is suppressed by capsaicin [8]. The earlier described blocking of voltage-activated calcium channels in hippocampal neurons by capsaicin [9] is also in line with this hypothesis.…”
Section: Resultsmentioning
confidence: 53%
“…Lack of TRPV 1 R-triggered release of radiolabeled neurotransmitters from synaptosomal preparations (D'Amico et al, 2004;Köfalvi et al, 2005Köfalvi et al, , 2007Cannizzaro et al, 2006;Ferreira et al, 2009) can be a result of the age of the animals used and/or of the lack of temporal resolution of the technique itself, i.e. that a fast-desensitizing capsaicin effect (Baamonde et al, 2005) is diluted in the minute-scale sampling process.…”
Section: Capsaicin Increases the Frequency Of Post-synaptic Excitatormentioning
confidence: 99%